ISSUES OF TAX CODE To influence of its shortcomings ON SETTLEMENT ADMINISTRATIVE tax dispute - Мацелик, Михайло Олексійович; Пригоцький, В'ячеслав Анатолійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article highlighted the serious weaknesses of the draft Tax Code from 21.09.2010 № 7101-1. Inparticular, the problems regulation simplified tax regime; moments income taxation and VAT taxexplanations of individual actions.